Negative Life Events, Social Ties, and Depressive Symptoms for Older Adults in China - Ruan, Hangqing; Shen, Ke; Chen, Feinian (Frontiers in Public Health, 2022)
With the rising prevalence rate of depression at old ages, a growing body of research has acknowledged negative life events as an important risk factor for depression, while less is known about how social ties play a role in cushioning the shock. Based on the panel data from a nationally representative elderly survey in China, our study reveals that negative life events indeed lead to increased depression severity for older adults. Social ties not only directly buffer depressive symptoms, but also attenuate the deleterious health consequences of negative life events. Our study further suggests the importance of distinguishing the types of social ties. It is the friendship ties, rather than family ties, that produces significant buffering effect. Moreover, the buffering effects of friendship ties are more prominent for less resilient and less privileged groups, namely male, rural, and less educated older adults. Our findings point to the importance of expanding and strengthening social networks for Chinese older adults in recovery from stress.